Serially Transplanted Nonpericytic CD146− Adipose Stromal/Stem Cells in Silk Bioscaffolds Regenerate Adipose Tissue In Vivo. (9th March 2016) - Frazier, Trivia P.; Bowles, Annie; Lee, Stephen; Abbott, Rosalyn; Tucker, Hugh A.; Kaplan, David; Wang, Mei; Strong, Amy; Brown, Quincy; He, Jibao; Bunnell, Bruce A.; Gimble, Jeffrey M.
Abstract: Progenitors derived from the stromal vascular fraction (SVF) of white adipose tissue (WAT) possess the ability to form clonal populations and differentiate along multiple lineage pathways. However, the literature continues to vacillate between defining adipocyte progenitors as "stromal" or "stem" cells. Recent studies have demonstrated that a nonpericytic subpopulation of adipose stromal cells, which possess the phenotype, CD45 − /CD31 − /CD146 − /CD34 +, are mesenchymal, and suggest this may be an endogenous progenitor subpopulation within adipose tissue. We hypothesized that an adipose progenitor could be sorted based on the expression of CD146, CD34, and/or CD29 and when implanted in vivo these cells can persist, proliferate, and regenerate a functional fat pad over serial transplants. SVF cells and culture expanded adipose stromal/stem cells (ASC) ubiquitously expressing the green fluorescent protein transgene (GFP-Tg) were fractionated by flow cytometry. Both freshly isolated SVF and culture expanded ASC were seeded in three-dimensional silk scaffolds, implanted subcutaneously in wild-type hosts, and serially transplanted. Six-week WAT constructs were removed and evaluated for the presence of GFP-Tg adipocytes and stem cells. Flow cytometry, quantitative polymerase chain reaction, and confocal microscopy demonstrated GFP-Tg cell persistence, proliferation, and expansion, respectively. Glycerol secretion and glucose uptake assays revealed GFP-Tg adipose was metabolically functional. Constructs seeded with GFP-Tg SVF cells or GFP-Tg ASC exhibited higher SVF yields from digested tissue, and higher construct weights, compared to nonseeded controls. Constructs derived from CD146 − CD34 + -enriched GFP-Tg ASC populations exhibited higher hemoglobin saturation, and higher frequency of GFP-Tg cells than unsorted or CD29 + GFP-Tg ASC counterparts. These data demonstrated successful serial transplantation of nonpericytic adipose-derived progenitors that can reconstitute adipose tissue as a solid organ. These findings have the potential to provide new insights regarding the stem cell identity of adipose progenitor cells.